Preferential effect of isoflurane on top-down vs. bottom-up pathways in sensory cortex - Raz, Aeyal; Grady, Sean M.; Krause, Bryan M.; Uhlrich, Daniel J.; Manning, Karen A.; Banks, Matthew I. (Frontiers in Systems Neuroscience, 2014)
The mechanism of loss of consciousness (LOC) under anesthesia is unknown. Because consciousness depends on activity in the cortico-thalamic network, anesthetic actions on this network are likely critical for LOC. Competing theories stress the importance of anesthetic actions on bottom-up ‘core’ thalamo-cortical (TC) versus top-down cortico-cortical (CC) and matrix TC connections. We tested these models using laminar recordings in rat auditory cortex in-vivo and murine brain slices. We selectively activated bottom-up vs. top-down afferent pathways using sensory stimuli in vivo and electrical stimulation in brain slices, and compared effects of isoflurane on responses evoked via the two pathways. Auditory stimuli in vivo and core TC afferent stimulation in brain slices evoked short latency current sinks in middle layers, consistent with activation of core TC afferents. By contrast, visual stimuli in vivo and stimulation of CC and matrix TC afferents in brain slices evoked responses mainly in superficial and deep layers, consistent with projection patterns of top-down afferents that carry visual information to auditory cortex. Responses to auditory stimuli in vivo and core TC afferents in brain slices were significantly less affected by isoflurane compared to responses triggered by visual stimuli in vivo and CC/matrix TC afferents in slices. At a just-hypnotic dose in vivo, auditory responses were enhanced by isoflurane, whereas visual responses were dramatically reduced. At a comparable concentration in slices, isoflurane suppressed both core TC and CC/matrix TC responses, but the effect on the latter responses was far greater than on core TC responses, indicating that at least part of the differential effects observed in vivo were due to local actions of isoflurane in auditory cortex. These data support a model in which disruption of top-down connectivity contributes to anesthesia-induced LOC, and have implications for understanding the neural basis of consciousness.